Hemophagocytic Lymphohistiocytosis and Inflammatory Bowel Disease: Case Report and Systematic Review - Brambilla, Bárbara (Inflamm Intest Dis, 2020)
AIM: To report a case of a female patient with hemophagocytic lymphohistiocytosis (HLH) and to systematically review the available cases of the association between HLH and inflammatory bowel disease (IBD). METHODS: In accordance to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, retrieval of studies was based on Medical Subject Headings and Health Sciences Descriptors, which were combined using Boolean operators. Searches were run on the electronic databases Scopus, Web of Science, MEDLINE (PubMed), Biblioteca Regional de Medicina, Latin American and Caribbean Health Sciences Literature, Cochrane Library for Systematic Reviews and Opengrey.eu. Languages were restricted to English, Spanish and Portuguese. There was no date of publication restrictions. The reference lists of the studies retrieved were searched manually. RESULTS: The search strategy retrieved 223 references. In the final analysis, 28 references were included, with the report of 35 cases. The most common clinical finding was fever, 57% of patients had a cytomegalovirus infection and 30 patients were on thiopurines previously to HLH diagnosis. Most patients were treated with steroids and antiviral therapy. All-cause mortality was 22%. CONCLUSION: These findings suggest that there might be a connection of HLH to IBD, opportunistic viral infections and the use of thiopurines. Due to the severity of such disease, the clinical suspicion is paramount to early diagnosis and therapy.